Identification of Constraints in Herbicide Application Technology of Punjab Farmers - Rajni; P K Sraw (Indian Journal of Extension Education, 2017)
Herbicides are the chemicals that are used to kill unwanted, undesirable, troublesome, noxious plants, called weeds. Ecological and environmental risks associated with their application in agriculture have been attracting the attention from the public as well as the scientific community. In order to reduce it, efforts have been made to identify the constraints prevalent in current herbicide application technology. The study on herbicide use and application technology was conducted in Amritsar and Jalandhar districts of Punjab and revealed that farmers generally depend upon local dealers for technical guidance. These dealers misguide the farmers for their own monetary benefits. Only 8 % of the farmers were generally aware of the meaning of chemical names of herbicides, rest depend more on popular names. About 5.3 % could differentiate between the classes of chemicals. The gaps in knowledge were identified and it was found that lack of awareness was with regard to spraying techniques, types of herbicides, time and method of application and dumping of empty containers. Poor communication was reported between farmers and extension persons. The study emphasized that with increasing brands in agriculture inputs and decreasing profitability, it becomes important that farmers should be trained specifically on spraying techniques and more knowledge regarding class and judicious use of herbicides be provided to them in farmer participatory mode.